1998
DOI: 10.1111/1467-9280.00064
|View full text |Cite
|
Sign up to set email alerts
|

When Words Compete: Levels of Processing in Perception of Spoken Words

Abstract: Current theories of spoken-word recognition posit two levels of representation and process: lexical and sublexical. By manipulating probabilistic phonotactics and similarity-neighborhood density, we attempted to determine if these two levels of representation have dissociable effects on processing. Whereas probabilistic phonotactics have been associated with facilitatory effects on recognition, increases in similarity-neighborhood density typically result in inhibitory effects on recognition arising from lexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

42
549
8
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 473 publications
(614 citation statements)
references
References 13 publications
42
549
8
4
Order By: Relevance
“…Considerable empirical evidence supports the view that, in languages such as English and Dutch (which has the same predominant word-stress pattern), listeners indeed follow the MSS in word segmentation (Cutler & Butterfield, 1992;Cutler & Norris, 1988;McQueen, Norris, & Cutler, 1994;Vroomen & de Gelder, 1995). Similarly, knowledge of native language phonotactic patterns has been suggested as another source of information about potential word boundaries in fluent speech (Brent & Cartwright, 1996;Cairns, Shillcock, Chater, & Levy, 1997;van der Lugt, 2001;McQueen, 1998;Vitevitch & Luce, 1998, 1999. For example, certain phonotactic patterns occur much more frequently between words than within the words of a language.…”
Section: Introductionmentioning
confidence: 96%
“…Considerable empirical evidence supports the view that, in languages such as English and Dutch (which has the same predominant word-stress pattern), listeners indeed follow the MSS in word segmentation (Cutler & Butterfield, 1992;Cutler & Norris, 1988;McQueen, Norris, & Cutler, 1994;Vroomen & de Gelder, 1995). Similarly, knowledge of native language phonotactic patterns has been suggested as another source of information about potential word boundaries in fluent speech (Brent & Cartwright, 1996;Cairns, Shillcock, Chater, & Levy, 1997;van der Lugt, 2001;McQueen, 1998;Vitevitch & Luce, 1998, 1999. For example, certain phonotactic patterns occur much more frequently between words than within the words of a language.…”
Section: Introductionmentioning
confidence: 96%
“…Immediate repetition paradigms have in fact been extensively used in psycholinguistic research to explore the structure of phonological and lexical representations. These studies have typically shown faster and more accurate performance for the repetition of words than for nonwords [the ''lexicality effect''; Hulme et al, 1991;Vitevitch and Luce, 1998;Vitevitch et al, 1999]. This advantage has been attributed to the recruitment of lexicosemantic knowledge during word but not nonword repetition.…”
Section: Introductionmentioning
confidence: 99%
“…Most interestingly, even repetition performance for nonword lists is influenced by the activation of sublexical language knowledge; this knowledge concerns the statistical properties of possible phoneme co-occurrences in a given language. Indeed, repetition of lists of nonwords containing phoneme co-occurrences that are frequent in native language phonology (highly wordlike stimuli) is faster and more accurate than repetition of nonwords composed of infrequent phoneme combinations (less wordlike stimuli) [see Gathercole et al, 1999;Majerus et al, 2004;Vitevitch and Luce, 1998 for a description of this ''phonotactic frequency effect'']. At a behavioral level, these lexicality and phonotactic frequency effects have been reported to be relatively preserved in AD [Peters et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Through competition, the word-recognition system can settle on an optimal parse of the speech input, even if signal-based cues are not present. The activation and competition of multiple lexical candidates are core mechanisms implemented by most models of spoken-word recognition (e.g., TRACE, McClelland & Elman, 1986;and Shortlist, Norris, 1994;see McQueen, 2005, for a review) and have received a great deal of empirical support (e.g., Allopenna, Magnuson, & Tanenhaus, 1998;Cluff & Luce, 1990;Connine, Blasko, & Titone, 1993;McQueen, Norris, & Cutler, 1994;Norris, McQueen, & Cutler, 1995;Tabossi, Burani, & Scott, 1995;Vitevitch & Luce, 1998Vroomen & de Gelder, 1995;Zwitserlood & Schriefers, 1995). In the English phrase play tennis, the words play, lay, late, and any, for example, would compete with each other.…”
mentioning
confidence: 99%